2018
DOI: 10.1590/1678-5150-pvb-5865
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of hydatidosis and cysticercosis in cattle in southern Rio Grande do Sul, Brazil, from 2013 to 2016

Abstract: Hydatidosis and cysticercosis are parasitoses caused by the larval forms of the cestodes Equinococcus spp. and Taenia spp., which belong to the Taeniidae family. Their definitive hosts are canids and humans, respectively, with ruminants as the intermediate hosts and humans as an accidental host of both diseases. These parasites are responsible for large economic losses in slaughterhouses due to condemnation of carcasses and by-products. The present study reports the mean incidence rates of hydatidosis and cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…In general, a reduction in occurrence rates was observed over the years, which was more pronounced for cysticercosis than for hydatidosis. The results corroborate the findings of Alberti et al (2018), who reported a decreasing trend in the occurrence of cysticercosis and hydatidosis from 2013 to 2016 in five municipalities in the southern region of the state of Rio Grande do Sul, probably due to the strengthening of communication and health education.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, a reduction in occurrence rates was observed over the years, which was more pronounced for cysticercosis than for hydatidosis. The results corroborate the findings of Alberti et al (2018), who reported a decreasing trend in the occurrence of cysticercosis and hydatidosis from 2013 to 2016 in five municipalities in the southern region of the state of Rio Grande do Sul, probably due to the strengthening of communication and health education.…”
Section: Discussionsupporting
confidence: 90%
“…Flooding of rivers or estuaries contaminated directly or indirectly by untreated sewage discharges indicates that contaminated water is among the main risk factors associated with disease transmission. Eggs can be transported by water over long distances, infecting animals that ingest it during the journey (Alberti et al 2018, Henckel et al 2020. Henckel et al (2020) reported that the regions with the highest risk of cysticercosis in the Rio Grande do Sul were Porto Alegre, Caxias do Sul, Santa Maria, Ijuí and Passo Fundo.…”
Section: Discussionmentioning
confidence: 99%
“…A set of 42 peer-reviewed published articles containing prevalence values (Additional file 2: Table S2) [7,11, and one describing the incidence of BCC in areas in Brazil was found in literature [59]. From these articles, we identified two articles [11,26] describing BCC prevalence in several Brazilian states, covering a long period and including a large sample size.…”
Section: Resultsmentioning
confidence: 99%
“…There was only one study performed in Brazil which describes the incidence of BCC from 2013 to 2016 in five Brazilian municipalities located in the state of Rio Grande do Sul (RS): Arroio Grande (0.72%), Canguçu (0.58%), Capão do Leão (1.31%), Pelotas (1.06%) and São Lourenço (0.83%) [59]. Furthermore, a set of 42 articles was found containing prevalence values and other additional information such as the period, method, state, administrative region, number of examined animals and number of cases (Additional file 2: Table S2).…”
Section: Incidence Prevalence and Spatial Distribution In Brazilmentioning
confidence: 99%
“…The temporal statistical analyses were done by using the Gretl 1.9.12 statistical software (GNU Regression, Econometricand Time-series Library), and an analysis of the existence of the trend and seasonality components was performed by verifying the series and their respective correlograms. Once verified the existence of these components, the series were differentiated and subsequently statistically tested for detecting analysis of stationarity, through increased Dickey-Fuller tests (Dickey & Fuller 1979), considering a value of p<0.05 (Morettin & Toloi 2006, Alberti et al 2018. Once analysis of stationarity was observed in the differentiated series, the presence or absence of the trend and seasonality components in the monthly series considered was inferred.…”
Section: Methodsmentioning
confidence: 99%